2018
DOI: 10.1183/13993003.00810-2018
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the airway microbiome in nontuberculous mycobacteria disease

Abstract: Aspiration is associated with nontuberculous mycobacterial (NTM) pulmonary disease and airway dysbiosis is associated with increased inflammation. We examined whether NTM disease was associated with a distinct airway microbiota and immune profile.297 oral wash and induced sputum samples were collected from 106 participants with respiratory symptoms and imaging abnormalities compatible with NTM. Lower airway samples were obtained in 20 participants undergoing bronchoscopy. 16S rRNA gene and nested mycobacteriom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
91
1
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(102 citation statements)
references
References 47 publications
(56 reference statements)
8
91
1
2
Order By: Relevance
“…These organisms, particularly fungi and Mycobacteria, present difficulties related to DNA extraction, as well as the lack of agreement on appropriate methods for sequencing and databases to identify micro-organisms. The widely used 16S rRNA sequencing methods used for microbiome studies do not identify Mycobacteria accurately [72]. SULAIMAN et al [72] studied a cohort of patients with NTM infection using 16S rRNA sequencing, and despite these patients being culture-positive for NTM, few mycobacteria were identified by sequencing.…”
Section: Several Viruses Including Influenza a And B Adenovirus Pamentioning
confidence: 99%
See 1 more Smart Citation
“…These organisms, particularly fungi and Mycobacteria, present difficulties related to DNA extraction, as well as the lack of agreement on appropriate methods for sequencing and databases to identify micro-organisms. The widely used 16S rRNA sequencing methods used for microbiome studies do not identify Mycobacteria accurately [72]. SULAIMAN et al [72] studied a cohort of patients with NTM infection using 16S rRNA sequencing, and despite these patients being culture-positive for NTM, few mycobacteria were identified by sequencing.…”
Section: Several Viruses Including Influenza a And B Adenovirus Pamentioning
confidence: 99%
“…The widely used 16S rRNA sequencing methods used for microbiome studies do not identify Mycobacteria accurately [72]. SULAIMAN et al [72] studied a cohort of patients with NTM infection using 16S rRNA sequencing, and despite these patients being culture-positive for NTM, few mycobacteria were identified by sequencing. There was an association between oral commensals and inflammatory responses, suggesting a modulating effect of other microbiota in NTM lung disease.…”
Section: Several Viruses Including Influenza a And B Adenovirus Pamentioning
confidence: 99%
“…As most NTM infections involve the MAC, previous studies evaluating the NTM-PD microbiome focused on the MAC. [20,28] We found that 16S rRNA sequencing identified mycobacteria in only 54.5% of bronchial washings and 27.3% of PSBs from NTM-PD patients (Supplementary Table 2). Previous studies reported that 16S…”
Section: Discussionmentioning
confidence: 89%
“…rRNA gene sequencing is not adequately sensitive, and technical improvements are needed. [28,29] Respiratory samples (especially PSBs) from NTM-PD patients tended to exhibit lower alpha diversities compared with those from control subjects. In a previous study, the alpha diversities of sputum samples from females with NTM-PD and those with both NTM-PD and breast cancer were significantly lower than those of samples from healthy females, consistent with our results.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation